Trend of Feline Medical Articles in SINTA 2-Accredited Veterinary Journals Published by Veterinary Medical Schools across Indonesia: A Systematic Review - Handoko, Jully; Alkausar, Triawan; Fitranda, Mulya; Suprayoga, Tito; Fani, Rifia Tiara; Putri, Frilianty; Ardhani, Fikri (Jurnal Sain Veteriner, 2025)
This systematic review aims to analyse the trends in feline medical articles published in veterinary journals by veterinary schools across Indonesia. Articles related to feline medicine were collected from SINTA 2-accredited veterinary journals. Out of 943 total articles, only 38 (4.03%) focused on feline medicine, indicating its limited attention. The number of feline medicine publications grew from 10 in 2022 to 20 in 2023, before dropping to 8 in 2024. Content analysis revealed that 50% of the studies were quantitative, 15.79% qualitative, and 34.21% mixed-methods. Study designs included case reports (39.47%), cross-sectional studies (23.68%), and surveys (13.16%), with a smaller proportion conducting RCTs, cohort studies, and reviews. Descriptive analysis (63.16%) was the most common data analysis technique, followed by t-tests, Chi-Square, and ANOVA. The research covered disciplines like internal medicine (47.37%), surgery (13.16%), and dermatology (10.53%). This review highlights the underrepresentation of feline medicine research in Indonesian veterinary journals and calls for a broader focus on this area to better address the medical needs of cats.